THE ECONOMICS OF COCONUT REPLANTING AND ASSOCIATED CROPPING (IN FIJI) - Dr. PATRICK MUMA (International Coconut Community, 1992)
The importance of coconut stems primarily from its being an export crop. Coconut largely constitutes a crop of convenience in the basically agricultural, mainly subsistence, essentially rural‑based economy of Fiji. It provides a basic dietary component and a source of cash income to meet social responsibilities, and employment opportunities in the various areas in which it is grown. Indeed, after sugar, coconut oil is Fiji's second most important agricultural export.